A pilot study examining the use of the autism diagnostic observation schedule in community-based mental health clinics. (December 2015) - Stadnick, Nicole; Brookman-Frazee, Lauren; Nguyen Williams, Katherine; Cerda, Gabrielle; Akshoomoff, Natacha
Highlights: We examined the use of the Autism Diagnostic Observation Schedule (ADOS) by community mental health providers with diagnostically complex youth suspected of Autism Spectrum Disorder (ASD) who received a diagnostic assessment. Results indicated that 57% of youths assessed received an ASD diagnosis. The utility of the ADOS was relatively strong and descriptively similar to data reported about the ADOS in other community samples. All discrepancies between ADOS classifications and final ASD diagnosis were false positives. In these cases, report narratives indicated that social communication difficulties identified on the ADOS were explained by symptoms of other mental health conditions. Abstract: Community-based mental health (CMH) services play an important, but relatively understudied role in the identification and treatment of youth with autism spectrum disorder (ASD) who may be receiving care for other psychiatric conditions. Little is known about the role of standardized ASD assessment measures administered by providers working in generalist community-based mental health (CMH) settings. This pilot study extracted data from three CMH clinics to examine the use of the Autism Diagnostic Observation Schedule (ADOS) by 17CMH providers who received ASD assessment training with 62 youth (Mean = 10.69 years) referred for an ASD diagnostic evaluation. Results indicated that 57% of youths assessed ultimately received an ASD diagnosis. All cases given a final ASD diagnosis were classified as "Autism" or "ASD" on the ADOS. Seventy percent of youth who did not receive a final ASD diagnosis were classified as "Non-Spectrum" on the ADOS. In these false positive cases, report narratives indicated that social communication difficulties identified on the ADOS were explained by symptoms of other mental health conditions (e.g., ADHD, anxiety). Future research is needed to examine the utility of the ADOS when used by CMH providers to facilitate CMH capacity to identify ASD.